Carbon nanotube sidewall functionalization with carbonyl compounds-modified birch conditions vs the organometallic reduction approach - Gebhardt, Benjamin; Syrgiannis, Zois; Backes, Claudia; Graupner, Ralf; Hirsch, Andreas; Hauke, Frank (Journal of the American Chemical Society, 2011)
Covalent addition reactions turned out to be one of the most important functionalization techniques for a structural alteration of single walled carbon nanotube (SWCNT) scaffolds. During the last years, several reaction sequences based on an electrophilic interception of intermediately generated SWCNT carbanions, obtained via Birch reduction or by a nucleophilic addition of organometallic species, have been developed. Nevertheless, the scope and the variety of potential electrophiles is limited due to the harsh reaction conditions requested for a covalent attachment of the functional entities onto the SWCNT framework. Herein, we present a significant modification of the reductive alkylation/arylation sequence, the so-called Billups reaction, which extends the portfolio of electrophiles for covalent sidewall functionalization to carbonyl compounds-ketones, esters, and even carboxylic acid chlorides. Moreover, these carbonyl-based electrophiles can also be used as secondary functionalization reagents for anionic SWCNT intermediates, derived from a primary nucleophilic addition step. This directly leads to the generation of mixed functional SWCNT architectures, equipped with hydroxyl or carbonyl anchor groups, suitable for ongoing derivatization reactions. A correlated absorption and emission spectroscopic study elucidates the influence of the covalent sidewall functionalization degree onto the excitonic transition features of carbon nanotubes. The characterization of the different SWCNT adducts has been carried out by means of Raman, UV-vis/nIR, and fluorescence spectroscopy as well as by thermogravimetric analysis combined with mass spectrometry and X-ray photoelectron spectroscopy analysis. © 2011 American Chemical Society.